Institutional Synergy in Village-Based Tourism Diversification: Governance Challenges in West Manggarai, Indonesia - DARMANTO Darmanto (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2026)
Tourism development in West Manggarai Regency remains highly dependent on Komodo National Park as the region’s flagship destination, creating economic vulnerability and limiting the development of alternative tourism areas. This study examines the contribution of institutional synergy in advancing the diversification of village-based tourism in West Manggarai, Indonesia. The research employs a qualitative case study approach focusing on Komodo National Park, Labuan Bajo, and Liang Dara Village. Data were collected through in-depth interviews with 19 informants, focus group discussions, field observations, and analysis of national and local policy documents. The findings indicate that tourism diversification remains limited due to fragmented institutional authority, weak cross-actor coordination, uneven tourism human resource capacity, limited accessibility, and insufficient integration of promotion strategies for non-Komodo destinations. Despite these challenges, Liang Dara Village demonstrates potential for developing nature-based, cultural, and handicraft tourism as part of integrated tourism packages. The study concludes that tourism diversification requires stronger institutional synergy among local government, the Labuan Bajo Flores Authority Agency (BPOLBF), village governments, tourism awareness groups, communities, and tourism businesses through institutionalized coordination, capacity strengthening, and integrated promotion strategies. This study contributes to tourism governance literature by highlighting the importance of institutional synergy in supporting tourism diversification in conservation-based destinations. Practically, the study recommends the establishment of formal coordination platforms among local government, BPOLBF, village governments, Pokdarwis, communities, and tourism businesses, alongside village capacity-building programs and integrated regional promotion strategies for non-Komodo destinations.